Relationship between dynamic visual acuity and multiple object tracking performance. (August 2022) - Vera, Jesús; Redondo, Beatríz; Molina, Rubén; Jiménez, Raimundo; Dalton, Kristine
We assessed the association between measures of dynamic visual acuity and a multiple object tracking task in physically active young adults. Ninety-four young adults performed the dynamic visual acuity and multiple object tracking tasks. Dynamic visual acuity was measured for horizontal and random walk motion paths at four target speeds (5, 10, 20, and 30°/s). For the multiple object tracking task, participants had to track three out of eight balls for 10 s, and the object speed was adjusted by a staircase procedure. We found that multiple object tracking performance was associated with better identification of horizontally and randomly moving targets in the dynamic visual acuity test ( p  < .001, r = −.35 [−.52, −.16]; and p  < .001, r = −.52 [−.65, −.35]; respectively). This effect was consistent across all target speeds (all p -values<0.05). However, static visual acuity did not correlate with any measure of dynamic visual acuity or multiple object tracking ( p  > 0.170 in all cases). This study provides novel insights into the association between the ability to identify horizontally and randomly moving targets and track multiple objects. Future studies are needed to determine the potential utility of dynamic visual acuity for talent identification and predicting sports performance in real-game situations.